INVESTIGATION OF ORGANIZATIONAL MODELS IN ORGANIC AGRICULTURAL PRODUCTION IN TURKEY (Third Sector Social Economic Review, 2020)
Farmers do in organic agricultural production come together with organic bazaars and other organizations and they both increase their own income and offer solutions to consumers’ wishes. There are some basic problems that limit the development in Turkey. One of the main problems is that the producers engaged in organic agriculture cannot come together through organization. In this study, the economic organization models have been examined in Turkey in order to contribute to the development of organic agricultural production and made various evaluations. This study has been prepared based on the literature; as a result of the literature review, present sources were examined, and interpretations were made by evaluating these sources from various angles. As a result; it has been determined that group-based organization on producer union is more than others in organic agricultural production in Turkey and fruit growing is the most with 8 unions in these groups. As a result of the research, it was seen that there are also cooperatives, Community Supported Agriculture model and producers associations besides producer unions.
Keywords: Organic agriculture; agricultural organization; organizational models; Turkey